Long term nitrofurantoin induced interstitial lung disease: a case series and literature review - Naureen, Samiha; Hart, Simon; Jawad, Nadia; Kennan, Nuala; Faruqi, Shoaib (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: In the UK, prophylactic use of nitrofurantoin is recommended in women who have 3 or more UTI per year. Reported cases of nitrofurantoin-induced pulmonary toxicity are limited and the exact mechanism of chronic nitrofurantoin induced lung reaction is unclear. In England, the national trend for prescribing Nitrofurantoin has gone up significantly in the last 10 years. We reviewed 10 cases of nitrofurantoin-induced pulmonary fibrosis diagnosed in last 8 years at our ILD Service. We aimed to reviewe patient demographics, time to presentation, lung function and imaging characteristics. Methods: We reviewed our ILD database from the year 2012 to 2020. 10 patients were identified diagnosed as Nitrofurantoin Induced Interstitial Lung Disease. All the cases were reviewed in MDT comprising Radiologists and clinicians with interest for ILD. We documented age, sex, initial renal function, eosinophil count, spirometry and radiology findings. In this case series, we focus on various CT findings and reversibility of radiological abnormality following cessation of Nitrofurantoin. Results: The mean age of our patient cohort is 80 years and all were female. The mean time to presentation from prescription was 17 months. Pre-treatment mean eGFR was 76ml/min/1.73m2.7 out of 10 patients had CT findings of ground glass opacity and traction bronchiectasis. 4 patients were treated with prednisolone. The patients in this series improved symptomatically with or without treatment with steroid following cessation of nitrofurantoin therapy, but irreversible changes in the chest imaging may contribute to long term morbidity. Conclusions: Cautious counselling should be undertaken prior to nitrofurantoin prescription regardless of renal function.